On Rough Covexsity Sets - Swealam, M.; Afify, R.A.; Sayed, M. El (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we introduced new concepts for surely and possibly , start shaped (convex ) set. Also for rough start shaped ( rough convex) set .We established the neccessary and sufficient conditions for a set to be star shaped (convex ) set or rough starshaped ( rough convex) set . Finally ,we introduced new concepts for star shaped (convex ) relation.